2008
DOI: 10.1371/journal.pone.0003138
|View full text |Cite
|
Sign up to set email alerts
|

Flowering Time Diversification and Dispersal in Central Eurasian Wild Wheat Aegilops tauschii Coss.: Genealogical and Ecological Framework

Abstract: Timing of flowering is a reproductive trait that has significant impact on fitness in plants. In contrast to recent advances in understanding the molecular basis of floral transition, few empirical studies have addressed questions concerning population processes of flowering time diversification within species. We analyzed chloroplast DNA genealogical structure of flowering time variation in central Eurasian wild wheat Aegilops tauschii Coss. using 200 accessions that represent the entire species range. Flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 26 publications
(36 reference statements)
3
92
0
Order By: Relevance
“…Previously, our group reported that extensive floweringtime variation was present among Ae. tauschii accessions (Matsuoka et al 2008). Early-flowering Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our group reported that extensive floweringtime variation was present among Ae. tauschii accessions (Matsuoka et al 2008). Early-flowering Ae.…”
Section: Discussionmentioning
confidence: 99%
“…The early-flowering accessions spread mainly in eastern habitats such as Afghanistan and Pakistan, implying that the early-flowering phenotype contributed to eastward dispersal and adaptation to these habitats in Ae. tauschii (Matsuoka et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although no appropriate cline, such as the geographic clinal pattern of flowering time found in the natural population of wild wheat Aegilops tauschii Cross. (Matsuoka et al 2008), was detected in wild barley population at this moment, some of the VRS1 isoforms which involve SAPs within well-conserved motifs are limited in their geographical distribution (Table 3). It is, therefore, possible that the function(s) of HvHox1 in wild barley may include adaptation to specific ecological conditions.…”
Section: Functional Diversity Of Alleles At Vrs1mentioning
confidence: 83%